2016
DOI: 10.1159/000444024
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Whole and Fat-Free Fluoridated Milk, Applied before or after Acid Challenge, against Dental Erosion

Abstract: This study analysed in vitro the effect of milk against dental erosion, considering three factors: the type of milk (bovine whole/fat-free), the presence of different fluoride concentrations and the time of application (before/after erosive challenge). Bovine enamel (n = 15/group) and root dentine (n = 12/group) specimens were submitted to the following treatments: after the first erosive challenge - 0.9% NaCl solution (negative control), whole milk with 0, 2.5, 5.0 and 10.0 ppm F, fat-free milk with 0, 2.5, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…A erosão dentária tem sido relatada por várias décadas 9 , no entanto a mudança nos hábitos alimentares e no estilo de vida da sociedade moderna 14 , com um aumento substancial no consumo de alimentos e bebidas potencialmente erosivos 15 , tem mudado sua frequência e a distribuição ao longo dos anos 9 , levando ao aumento de sua prevalência e tornando-a uma condição mais comum 4 . Quando em contato com a superfície dentária os ácidos acarretam a dissolução do tecido duro inorgânico, ocasionando diminuição da resistência mecânica e redução da dureza da camada superficial 11 .…”
Section: Resultados O Erosãounclassified
See 1 more Smart Citation
“…A erosão dentária tem sido relatada por várias décadas 9 , no entanto a mudança nos hábitos alimentares e no estilo de vida da sociedade moderna 14 , com um aumento substancial no consumo de alimentos e bebidas potencialmente erosivos 15 , tem mudado sua frequência e a distribuição ao longo dos anos 9 , levando ao aumento de sua prevalência e tornando-a uma condição mais comum 4 . Quando em contato com a superfície dentária os ácidos acarretam a dissolução do tecido duro inorgânico, ocasionando diminuição da resistência mecânica e redução da dureza da camada superficial 11 .…”
Section: Resultados O Erosãounclassified
“…Assim sendo, o principal objetivo dos estudos que envolvem erosão é a busca de um mecanismo eficaz no aumento da deposição mineral no esmalte superficial amolecido e, principalmente na redução da desmineralização, promovendo uma camada resistente contra o efeito dos ácidos responsáveis pela erosão 32 . Nesse contexto, o uso de técnicas que minimizem a perda mineral do esmalte dentário através do fortalecimento da superfície dentária contra a desmineralização 4 , tem sido cada vez mais estudado dentre as quais o emprego de proteínas, a exemplo da caseína 14 , cuja ação como agente anti-erosivo tem ganhado destaque 33 .…”
Section: Resultados O Erosãounclassified
“…With respect to the association between ETW and milk consumption, our results are similar to those obtained in a meta-analysis published in 2015 [7] where the consumption of milk was associated with ETW. Milk has a high concentration of calcium, phosphate, and casein, which protect the dental surface against hydroxyapatite dissolution [9,10]; moreover, its lipid and protein content adheres to the dental surface, acting as a barrier against acids that are able to reach the oral cavity through extrinsic or intrinsic sources [11]. Also, Corrêa et al [43] found, in a group of 2-20-year-old Brazilians, that the odds of exhibiting ETW in anterior teeth were 60% lower (OR = 0.40) in those who frequently drank milk compared with those who had a lower consumption.…”
Section: Discussionmentioning
confidence: 99%
“…These minerals protect the dental surface against hydroxyapatite demineralization [9,10]. Additionally, their lipids and proteins can adhere to the tooth surface, working as a protective barrier against acids [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other components in milk, such as protein, fat and other minerals may influence its protective effect, possibly because they serve as a physical barrier against the acids or buffer related caries initiation and progression. 50,51 A dose-dependent effect of fluoridated milk was reported. 52 Patients with hyposalivation or who have undergone radiotherapy in the head and neck region are at high risk for root caries because of the reduction in salivary flow rate.…”
Section: Author Manuscriptmentioning
confidence: 99%